Music-based interventions in the treatment of eating disorders: a scoping review - Heiderscheit, Annie; Gawronska, Julia; Bloska, Jodie; Ragnhildstveit, Anya; Milton, Thandi; Neufeld, Sharon A. S. (Frontiers in Psychiatry, 2025)
IntroductionEating disorders (EDs) are potentially life-threatening conditions characterized by persistent eating- and body-related disturbances that negatively impact nutritional intake, psychological well-being, and physical health. While psychological therapies remain the primary treatment for patients with EDs, music-based interventions (MBIs) show significant promise for addressing symptoms in clinical practice. However, little is known about the methods employed in these interventions or their effectiveness in addressing or improving ED outcomes.MethodsFollowing PRISMA-ScR guidelines, we conducted a scoping review of the literature. Eight electronic databases were systematically queried from inception to May 2025 for studies evaluating MBIs in patients engaged in ED treatment. Data regarding study design, sample characteristics, intervention components, and primary outcomes were extracted and analysed utilising either reflexive thematic analysis or descriptive statistics. The quality of intervention reporting was additionally examined utilising the established MBI reporting guidelines.ResultsOf the 114 articles screened, 21 met inclusion criteria. The final sample comprised 10 case studies, 6 qualitative studies, 4 quantitative studies, and 1 mixed methods study, with all but one conducted in high-income countries. Settings included inpatient (n = 12), outpatient (n = 7), and combined (n = 2) ED programs. Most MBIs involved music therapy (n = 18), while others incorporated vibroacoustic therapy (n = 1), background music during mealtimes (n = 1), and group singing (n = 1). Delivery formats encompassed individual (n = 14), group (n = 5), and hybrid (n = 1) sessions, or were not indicated. Qualitative synthesis identified seven themes reflecting symptom management, self-development, and treatment engagement. Quantitative studies reported improvements in anxiety, mood, ED symptoms and increased food eaten and weight gain. However, robust conclusions were limited by small sample sizes, a lack of control group, non-randomisation, or another intervention being implemented with the MBI. Overall, reporting of MBI components was inconsistent, with a mean completeness of 45–100%.DiscussionTo our knowledge, this is the largest scoping review to map the breadth and depth of studies assessing MBIs in ED treatment. Preliminary evidence supports positive psychological and behavioural outcomes for patients with EDs. However, conclusions are limited by lack of methodological rigor, variable outcome measures, and inconsistent reporting of intervention components or theoretical framework. The complex and multifaceted nature of EDs and high rates of comorbidities and trauma histories further complicates interpretations. To advance research and clinical application of MBIs in ED care, standardized approaches to intervention design and reporting are needed, as well as randomised controlled studies clearly testing MBIs against other interventions.